The Older Finnish Twin Cohort — 45 Years of Follow-up. (29th August 2019) - Kaprio, Jaakko; Bollepalli, Sailalitha; Buchwald, Jadwiga; Iso-Markku, Paula; Korhonen, Tellervo; Kovanen, Vuokko; Kujala, Urho; Laakkonen, Eija K.; Latvala, Antti; Leskinen, Tuija; Lindgren, Noora; Ollikainen, Miina; et al.
Abstract: The older Finnish Twin Cohort (FTC) was established in 1974. The baseline survey was in 1975, with two follow-up health surveys in 1981 and 1990. The fourth wave of assessments was done in three parts, with a questionnaire study of twins born during 1945–1957 in 2011–2012, while older twins were interviewed and screened for dementia in two time periods, between 1999 and 2007 for twins born before 1938 and between 2013 and 2017 for twins born in 1938–1944. The content of these wave 4 assessments is described and some initial results are described. In addition, we have invited twin-pairs, based on response to the cohortwide surveys, to participate in detailed in-person studies; these are described briefly together with key results. We also review other projects based on the older FTC and provide information on the biobanking of biosamples and related phenotypes.